The Impact of Surface and Deep Acting on Employee Creativity. Issue 3 (2nd July 2020) - Hill, N. Sharon; Zhang, Hongping; Zhang, Xiaomeng; Ziwei, Yang
ABSTRACT: Given the increased need for collaboration to achieve greater speed and flexibility in responding to organizations' environmental demands, there is growing interest in understanding the implications of collaborative work for employee creativity. This study examines how emotion work (i.e., regulating emotions in a social context) that helps to meet the interpersonal demands of collaboration relates to employee creativity. Conservation of resources theory is used to hypothesize a moderated mediation model where two emotion work strategies – surface acting and deep acting – are indirectly related to creativity through the mediating effect of affective commitment, with psychological safety as a moderator of this indirect relationship. Survey data collected from 546 employees in 42 workgroups in a high-tech manufacturing company in China were analyzed using hierarchical linear modeling and bootstrapping procedures. Results showed that surface acting and deep acting are, respectively, negatively and positively related to creativity through the mediating effect of affective commitment. Also, psychological safety strengthened the positive relationship between affective commitment and creativity, resulting in a moderated mediation effect whereby psychological safety moderates the indirect effect of surface acting and deep acting on creativity through affective commitment. The implications of these findings for emotion work and creativity research are discussed.